2007
DOI: 10.1074/mcp.m600129-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Analysis of the Native Protein Complex Containing Actinin-4 in Prostate Cancer Cells

Abstract: Actinin-4 was originally identified as an actin-binding protein associated with cell motility and cancer invasion and metastasis. However, actinin-4 forms complexes with a large number of different partner proteins and is speculated to have several distinct functions depending on its partner. The level of actinin-4 expression was found to be significantly lower in prostate cancer cells than in non-cancerous basal cells, and restoration of actinin-4 expression inhibited cell proliferation by prostate cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 46 publications
2
38
1
2
Order By: Relevance
“…In addition to the kidney-specific phenotype of actinin-4-deficient mice, the tissue-specific regulation of actinin-4 function is suggested by several cancers. While elevated actinin-4 expression mediates tumor progression of colorectal and non-small lung cell cancers, the tumor suppressive effect of actinin-4 is observed with neuroblastoma and prostate cancer cells (12,14,33,53). Although the molecular mechanism for the lack of widespread epithelial dysfunction outside the kidneys remains elusive, highly homologous actinin-1 and/or many actinin-4-binding proteins are expected to play an important role in compensating for the actinin-4 deficiency outside of the kidneys in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the kidney-specific phenotype of actinin-4-deficient mice, the tissue-specific regulation of actinin-4 function is suggested by several cancers. While elevated actinin-4 expression mediates tumor progression of colorectal and non-small lung cell cancers, the tumor suppressive effect of actinin-4 is observed with neuroblastoma and prostate cancer cells (12,14,33,53). Although the molecular mechanism for the lack of widespread epithelial dysfunction outside the kidneys remains elusive, highly homologous actinin-1 and/or many actinin-4-binding proteins are expected to play an important role in compensating for the actinin-4 deficiency outside of the kidneys in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In human prostate cancer cell lines (22RV1, PC-3, LNCaP) ACTN4 protein product was less abundant than in normal human prostate epithelial cells, an observation that is conflicting with the findings in the most reports investigating relationship ACTN4-cancer development. Increasing the level of α-actinin 4 in those prostate cancer cells markedly suppressed cell-growth (Hara et al, 2007). In the same report the authors propose disturbance in clathrin-mediated endocytosis as the main mechanism associated with α-actinin 4 mediated cellular effects.…”
Section: Prostate Cancermentioning
confidence: 51%
“…α-Actinin has been found in isolated plasma membranes containing clathrin (Burridge et al, 1980) and association of α-actinin 4 and clathrin heavy chain has been identified in prostate cancer cells. Overexpression of α-actinin 4 facilitated transferrin endocytosis (Hara et al, 2007). v/ Function in glomerular podocytes.…”
Section: Functionmentioning
confidence: 99%
“…ACTN4 interacts with HDAC7 by its C-terminal calmodulin (CaM) -like domain, and activates ERα transcription, which contributes to tumorigenesis in breast cancer (42). In addition, elevated levels of ACTN4 are widely identified in other malignancies, including colorectal, pancreatic, prostate and ovarian cancer, salivary gland carcinoma and esophageal cancer (38,(42)(43)(44)(45)(46).…”
Section: Nuclear Abps In Cancer Cellsmentioning
confidence: 99%